Interlingual and Intralingual Errors of Descriptive Writing Produced by Vocational School in Denpasar - Ines Marylena Candra Manik, Ni Putu; I Kadek Darmo Suputra (International Journal of Instructions and Language Studies, 2024)
In curriculum in Indonesia, writing is one of the skills taught in English subject. The common problems faced by students in composing English sentence were interlingual errors and intralingual errors. This study aimed to analyze the students' interlingual and intralingual interferences of Vocational Students’ descriptive writing. A qualitative approach was applied by examining the students' descriptive writing. There were 30 students’ writings as object of study. Data collection was done through reading, note-taking, classifying, and describing. The results of study revealed that the most frequent interlingual form produced by the students was subject-verb agreement. Meanwhile the frequent intralingual form found was overinclusion. To sum up, interlingual and intralingual interferences were found in the students' descriptive writing